New proposals to strengthen the boom of agriculture in Peru: massive use of genetic resources and development of modern breeding programs - Arbizu Berrocal, Carlos Irvin (2021)
Peru is a place with abundant biological resources that should be employed for the benefit of society in general. However, to date, the use of Peruvian plant genetic resources was not fully exploited for the development of improved crops. This work was mostly conducted by the international private sector. The Climate Change Laboratory at Instituto Nacional de Innovación Agraria, and other laboratories at Universidad Nacional José Faustino Sánchez Carrión and Universidad Nacional Agraria La Molina together with other research programs of other institutions seek to promote the massive and sustainable use of plant genetic resources maintained in germplasm banks. It is planned to make use of modern molecular and morphological techniques. Moreover, infrastructure and human resources are being improved. As a result, we will be able to maintain the growth of the agricultural activity in Peru in terms of space and time.